1997
DOI: 10.1021/la970243d
|View full text |Cite
|
Sign up to set email alerts
|

Order in Thin Films of Side-Chain Liquid-Crystalline Polymers

Abstract: Spin-coated side-chain liquid-crystalline polymer films, based on alternating copolymers of maleic anhydride and α-olefins carrying terminal mesogenic methoxybiphenylyloxy groups, on silicon wafers show lamellar ordering upon annealing above the glass transition temperature. In the surface topography (atomic force microscopy measurements), structures are visible with a height corresponding to a bilayer. Also within the film, the side chains are ordered perpendicularly to the surface as measured by X-ray reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 8 publications
4
27
0
Order By: Relevance
“…Compared with the vast amount of studies for amorphous and crystalline (LC) polymers, studies on the anomaly in structure and orientation of side chain liquid crystalline polymers in ultrathin film states are rather unexplored. However, some significant data have been reported. Henn et al discussed the orientational change in mesogens of a smectic polymer at a ultrathin film state by X-ray reflectometry measurements. They observed that the homeotropically aligned rod mesogens becomes planar for films below 10 nm when the film is in the smectic C* phase.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the vast amount of studies for amorphous and crystalline (LC) polymers, studies on the anomaly in structure and orientation of side chain liquid crystalline polymers in ultrathin film states are rather unexplored. However, some significant data have been reported. Henn et al discussed the orientational change in mesogens of a smectic polymer at a ultrathin film state by X-ray reflectometry measurements. They observed that the homeotropically aligned rod mesogens becomes planar for films below 10 nm when the film is in the smectic C* phase.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the dewetting process strongly depended on the molecular structure properties 52, 53. Lee et al has reported the solvent‐driven dewetting of PS and the rim instability 42.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in addition to ordinary linear polymers, end-functionalized polymer, block copolymers, star polymers, and ring polymers are also interesting class of polymer materials for dewetting processes. Additionally, the dewetting behavior of LC polymers has aroused another interest, i.e., a hierarchical LC-ordered structure involved during the dewetting process. …”
Section: Introductionmentioning
confidence: 99%